Conceptual review of the empirical link between relational social capital, intrapreneurship and performance of multinational corporations in Malaysia - the mediating role of intrapreneurship - Yeoh, Khar Kheng; June, Sethela (2015)
Thee changes taking place at the workplace especial@ in major business corporations has created a situation whereby no single corporate manager or single functional expert can be expected to prosses the vast and #ten complex knowledge or know m to contribute to the success of the organization. Efective cwpwafe managers realize that deyelqiprg an extensive and diverse netvork of relationships is paramount to thkr abilify fo wntn'bute to the organization. Therefore, the accumulation of tacit knowledge among corporate managers through a robust social capital within an organization will lead to the creation of new products, new services, and new business processes that will contribute positively to the bottom line of the multinational corporations. This paper represents an attempt to integrate the concept of intrapreneurs59 with the literature on social capital by examining the impact of relational social capital through intrapreneurship in thepe$rmance of multinational corporations. In short, corporate manager (intrapreneur) in multinational corporations should use sociaIcapitafas a resource to further leverage the organizational performance in this higly competitive business world. In addition, this paper specifically investigates the entropy of social capital in the context of corporate environment among the managerial staff and its implications towards multinational corporation performance Malaysia.